DAMPAK SISTEM PEMBELAJARAN DARING TERHADAP KEGIATAN BELAJAR MENGAJAR PADA MASA PANDEMI COVID 19 DI SDN 3 SRIMINOSARI - Nurul Hidayah (AS-SALAM, 2020)
This article aims to describe the impact of teaching and learning activities using an online learning system during the Covid 19 pandemic at SDN 3 Sriminosari, Labuhan Maringgai District. This research uses descriptive qualitative method, data collection is done by interview, documentation and observation. The results showed that the impact of teaching and learning activities with the online learning system during the Covid 19 period led to increased parental concern for children in accompanying learning activities and breaking new clusters of the spread of Covid 19, but this was not matched by good children's learning outcomes this was due to not all teachers and parents of students are able to operate technology, weak internet networks, unstable public financial conditions, no moral guidance from teachers, and the material presented is very unattractive to students. The expected positive impact of this article as a media of information requires that it is necessary to be prepared to implement an online learning system by paying attention to supporting facilities and infrastructure; and socialization of applications used in learning activities so that all users can use them well.